2007
DOI: 10.1128/jvi.02467-06
|View full text |Cite
|
Sign up to set email alerts
|

A Borna Disease Virus Vector for Expression of Foreign Genes in Neurons of Rodents

Abstract: An expression cassette for green fluorescent protein was successfully inserted at a site near the 5′ end of the genome of Borna disease virus (BDV). When introduced into a mutant virus with highly active polymerase, the foreign gene was strongly expressed in neurons of infected rats. Since BDV can establish long-term persistence in the central nervous system of rodents, it may be used to engineer efficient vectors for specific delivery of foreign genes into highly differentiated neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…A previous study by Schneider et al showed that replication-competent rBDV was not able to be rescued when an extra transcription unit was inserted into the P/M region of the BDV genome (26). To examine further the availability of the P/M region for expression of a foreign gene, we inserted a GFP cassette into the site as indicated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study by Schneider et al showed that replication-competent rBDV was not able to be rescued when an extra transcription unit was inserted into the P/M region of the BDV genome (26). To examine further the availability of the P/M region for expression of a foreign gene, we inserted a GFP cassette into the site as indicated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recombinant BDV (rBDV) with green fluorescent protein (GFP) near the 5Ј end of the genome (rBDV 5ЈGFP) successfully infected, and was propagated in, cultured cells. This study suggested that the 5Ј end of the BDV genome might be the only site for insertion of the GFP expression cassette because rBDV could not be rescued after introduction of the cassette into other regions of the genome (26). On the other hand, a recent study using the rBDV 5ЈGFP revealed that the termination signal upstream of the GFP gene is modified by insertion of additional A residues, resulting in downregulation of GFP expression within several weeks of infection of rat brains (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A similar transcription pattern was previously observed in cells infected with BDV mutants carrying distinct alterations in this region of the genome (Poenisch et al, 2008b), indicating that the second-site mutations of BDV-X59 # 1 might have a negative effect on the efficient use of the T1 transcriptional termination signal. No such compensatory mutations were previously observed in a Vero cell-grown BDV variant expressing the green fluorescent protein (Poenisch et al, 2007;Schneider et al, 2007), indicating that overexpression of X generates a nonfavourable condition which the virus tries to evade.…”
mentioning
confidence: 96%
“…1a). From previous work we know that foreign genes can be expressed from this genome position if flanked by S3 transcription start and T4 transcription termination signals (Poenisch et al, 2007;Schneider et al, 2007). Two independent experiments aimed at rescuing the corresponding virus (designated BDV-X59) were performed using previously described technology (Martin et al, 2006;Poenisch et al, 2008a).…”
mentioning
confidence: 99%